2009
DOI: 10.1016/j.jmaa.2008.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Population models with diffusion, strong Allee effect and constant yield harvesting

Abstract: We study the steady state distribution of reaction diffusion equations with strong Allee effect type growth and constant yield harvesting (semipositone) in heterogeneous bounded habitats. Assuming the exterior of the habitat is completely hostile, we establish existence results for positive solutions. We also establish a multiplicity result for the non-harvested case. We obtain our results via the method of sub-super solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Population models with different harvesting strategies have been studied by scholars, for example, impulsive harvesting [38][39][40][41][42][43][44], constant rate harvesting [45][46][47][48], optimal harvesting strategy [49], linear harvesting [50,51], and nonlinear harvesting [52,53]. Volterra's model [24] and Cushing's model [25] can sufficiently describe the deterministic dynamical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Population models with different harvesting strategies have been studied by scholars, for example, impulsive harvesting [38][39][40][41][42][43][44], constant rate harvesting [45][46][47][48], optimal harvesting strategy [49], linear harvesting [50,51], and nonlinear harvesting [52,53]. Volterra's model [24] and Cushing's model [25] can sufficiently describe the deterministic dynamical behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Upadhyay et al [2011] proposed a reaction-diffusion model to study the dynamics of phytoplankton-zooplankton system in which the consumption of phytoplankton species follows the Beddington-DeAngelis type of functional response and found that the instability observed in the model aquatic system is diffusion driven and fish predation acts as a regularizing factor. A population model with diffusion, strong Allee effect and constant yield of harvesting has been studied by Ali et al [2009]. Spatiotemporal complexity of a three-species ratio-dependent food chain model has been proposed by Rao [2014] and he observed the sequences of cold spots → stripespots mixtures → stripes → hot stripes-spots mixtures → hot spots → chaotic wave patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The existence, nonexistence and/or multiplicity of positive solutions to problem (P λ ) have been studied extensively in the literature; see, for example, [1,2,5,6,8,9,[11][12][13][14][15][17][18][19][20][21][22][23][24][25] and the references therein. In many previous studies, the nonlinear function f (x, s)/s p−1 was assumed to be nonincreasing in s, and under this condition, it can be shown that problem (P λ ) has at most one positive solution (see, e.g., [1,6,8,9,22]).…”
Section: Introductionmentioning
confidence: 99%